2016
DOI: 10.1016/j.clay.2016.01.017
|View full text |Cite
|
Sign up to set email alerts
|

Montmorillonite colloids: II. Colloidal size dependency on radionuclide adsorption

Abstract: Bentonite is a strong radionuclide (RN) adsorbent. As a consequence, it is proposed as one of the engineered safety barriers in many concepts of nuclear waste disposal in granite formations. Nevertheless, in contact with groundwater of low ionic strength, montmorillonite colloids may be released from the bentonite buffer and transported towards the biosphere. During the transport of colloids in bedrock fractures, size separation of clay colloids may occur, that may potentially also affect the RN mobility. In t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(3 citation statements)
references
References 54 publications
(56 reference statements)
0
3
0
Order By: Relevance
“…The adsorption of Th (IV), U (VI), Np (V), Tc (VII), and Pu (IV) on fractionated fractions of montmorillonite in synthetic carbonated groundwaters was studied. Montmorillonite colloids obtained by fractionation of crude clay material in the presence of organic matter at the initial stage of separation, there is a significant decrease in the absorption of Th and Pu [20].…”
Section: Resultsmentioning
confidence: 99%
“…The adsorption of Th (IV), U (VI), Np (V), Tc (VII), and Pu (IV) on fractionated fractions of montmorillonite in synthetic carbonated groundwaters was studied. Montmorillonite colloids obtained by fractionation of crude clay material in the presence of organic matter at the initial stage of separation, there is a significant decrease in the absorption of Th and Pu [20].…”
Section: Resultsmentioning
confidence: 99%
“…Biomineralization refers to the process that an organism constructs a hierarchical structure based on inorganic minerals under certain environmental conditions [1,2,3,4,5]. This process is highly regulated by the biological environments that guide mineral nucleation and growth, including solution states, biomacromolecules, and substrates [6,7,8]. Although the main components of many mineralized tissues are the inorganic phases regulated by the upper biological environment during crystallization and growth.…”
Section: Introductionmentioning
confidence: 99%
“…Ø 70.3 Highly variable REE content, mostly flat Chondrite normalized profile Highly variable REE content, significant LREE enrichment minerals(Kretzschmar and Schäfer 2005;Bouby et al 2008;Norrfors et al 2016) is widely observed in ground waters.…”
mentioning
confidence: 99%